Real-time naked-eye multiplex detection of toxins and bacteria using AIEgens with the assistance of graphene oxide. (5th December 2016) - Zhang, Ruoyu; Cai, Xiaolei; Feng, Guangxue; Liu, Bin
Abstract : Toxins and bacteria in water or food pose a threat to human life and could potentially be exploited for bioterrorism. Real-time naked-eye detection of these contaminants is highly desirable to provide a direct and simple analytical method and address the challenges of the existing strategies. Using the detection of ricin and B. subtilis as an example, a naked-eye multiplex detection model is established. In this work, a green fluorogen with aggregation-induced emission (AIE) characteristics was encapsulated in silica nanoshells. The resulting green AIE nanoparticles (NPs) were further functionalized with ricin binding aptamers (RBA), which were used together with graphene oxide (GO) to provide a fluorescence turn-on approach recognizable by naked eye for the specific sensing of ricin. The platform is compatible with a red emissive fluorescent light-up probe (AIE-2Van) for B. subtilis detection. The success of the multiplex is validated by different colours, that is, green for ricin and red for B. subtilis, which are clearly recognizable by naked eye in the same solution.